Nonsteady Heat Loses to the Ground from a Building with Heated Underground Floor or Slab on Ground. Issue 4 (March 2021) - Levin, E; Okunev, A
Abstract: Numerical model and research results of nonsteady heat transfer between building and ground basement are in the article. Two most common cases of heat contact between building and ground basement are compared: building with heated underground floor and building on the slab on ground. Nonsteady heat loses over period about several years of building exploitation are analyzed that made possible to establish a patterns of heat transfer between building and ground with taking into account of ground around of building inertness. Heat loses from building represented using mean values at the one unit of length of building perimeter. In case of building with underground floor calculated nonsteady heat loses of floor and underground wall are shown. Also shown results of nonsteady heat transfer to ground from outdoor air and groundwater. Numerical methodic used in research based on explicit finite-difference method applicated to boundary value problem of nonsteady heat transfer in ground. The problem taking into account existence of moveable groundwater without heat transfer calculation in the volume of groundwater.